Optimal Emergency Ordering Policy for Inventory with a Random-Ending-Time Supply Disruption. (27th May 2022) - Hu, Man; Guo, Libin
Abstract : This paper considers the emergency ordering strategy for the classical economic ordering quantity inventory system with a supply disruption. For situations where the ending time of supply disruption is stochastic and the purchase price increases over time during that period, we develop an emergency ordering optimization model based on maximizing retailer's profits. Through modeling analysis in various situations, the closed-form solution of the model is obtained, and the optimal emergency ordering strategy is provided for retailers. Numerical experiments verify the effectiveness of the model and the influence of related parameters on the optimal ordering strategy.